Change in geographic access to community health centers after Health Center Program expansion. (1st April 2019) - Evans, Leigh; Charns, Martin P.; Cabral, Howard J.; Fabian, M. Patricia
Abstract : Objective: To examine geographic access to community health centers (CHC accessibility) before and after Health Center Program expansion in three Southern states. Data Sources: Community health center data were from the Health Resources and Services Administration (1967‐2016). Population estimates and sociodemographic characteristics were from the American Community Survey (2006‐2015). Study Design: We used the two‐step floating catchment area method to calculate CHC accessibility for census tracts in 2008 and 2016. We mapped census tract‐level variation and used spatial regression to assess to what extent indicators of potential CHC need were associated with change in accessibility from 2008 to 2016. Principal Findings: Community health center accessibility increased by 192 percent overall, and the proportion of tracts with no accessibility decreased by 65 percent. Indicators of potential need were not associated with greater gains in CHC accessibility from 2008 to 2016, but census tracts with less accessibility at baseline saw larger accessibility increases. Conclusions: Community health center accessibility substantially increased from 2008 to 2016, but increases did not differentially impact groups with greater potential need. This approach for measuring CHC accessibility offers significant improvement in granularity over traditional CHC accessibility measures.